Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset listing the 21058 species recorded in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Observation", "BasisOfRecord is Specimen" ] }, "Country is Russian Federation", "Year 1990-2012", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset's 21058 records were derived from 369 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003710-200221144449610/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences